Karakteristik Siswi Dengan Kejadian Anemia Pada Remaja Putri di Kota Makassar - Ruqaiyah Ruqaiyah; Ayatullah Harun; Fatmawati Amir; Ali Imran (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Anemia is a global health issue that is commonly found among adolescent girls, especially in developing countries. Anemia occurs when hemoglobin levels in the blood are below normal, thereby disrupting oxygen transport to all body tissues. Makassar, as a large city with diverse socioeconomic backgrounds, still faces the problem of anemia among female students that has not been optimally addressed. Based on several local surveys, it was found that adolescents from lower-middle socioeconomic backgrounds and those with low nutritional knowledge tend to have a higher risk of developing anemia. This study aims to identify the characteristics of female students that contribute to the incidence of anemia among adolescent girls in Makassar City. The research method used is an analytical study with a cross-sectional approach conducted on 60 female students in Makassar City using simple random sampling in March 2023. The variables studied included father's education, mother's education, parental income, nutritional knowledge, and hemoglobin levels. Data were collected through questionnaires and hemoglobin measurements, and the data were analyzed using the chi-square test. The results of the study showed that there was no significant relationship between father's and mother's education, family income, and nutritional knowledge with the incidence of anemia among female students. The conclusion of this study emphasizes the need to strengthen behavior-based nutritional interventions and practical nutrition literacy, not just educational and informative ones. Although education and nutrition knowledge are important, the findings indicate that knowledge alone is insufficient to prevent anemia if not followed by proper dietary practices. Keywords: anemia, hemoglobin, characteristics, female students